Pembelajaran berbasis tutor sebaya pada Matakuliah Ilmu Ukur Tanah dan Lab - Taufiq Natsir (Seminar Nasional LP2M UNM, 2019)
Students' graduation in the Land Measure subject is mostly caused by students not completing their assignments or practice reports thoroughly, where practice reports are a prerequisite for taking the Semester Final Examination, namely students who do not exceed 60% completion of their practice report. in determining the final value where the final value is determined by the average value of the Quiz, UTS, Tasks and UAS. This study used a randomized control group pretest-posttes design with a total sample of 72 students consisting of 37 in the experimental class and 35 in the control class. Data analysis using t-test. Based on the test criteria, it was concluded that there was a significant effect on student learning outcomes in the class using peer tutoring learning methods